The Histological Evaluation of the Testes of Rats which Applied Formaldehyde and Lavender Oil - Köse, Evren; Sarsılmaz, Mustafa; Meydan, Sedat; Pekmez, Hıdır; Dabak, Durrin Özlem; Ögetürk, Ahmet Kavaklı Murat (İnönü Üniversitesi, 2010)
[EN] Aim: In our study, harmful effects of formaldehyde (FA) inhalation on the testes were investigated histologically. In addition, the possible protective effects of lavender oil which often used in aromatherapy, were examined against these damages. Material-Methods: For this purpose, 21 albino-Wistar rats were used. The rats of group I was used as control group. The rats of group II were exposed FA (10 ppm/ 1hour) for 35 days. The rats of group III inhaleted lavender oil (1ml/1 hour) with FA. At the end of the experiment, all rats were sacrified and testes were removed for histological examination. In this examination, the diameters of seminiferous tubul, Leydig cells and Leydig cells with damaged nucleus were determined. Results: When the rats were exposed to formaldehyde compared with the control group, it was determined that the diameter of tubuls and number of Leydig cells were decreased and Leydig cells with damaged nucleus were increased. And also it was seen that there were atrophic changes in the tubuls. In the group in which the lavender oil was applied with formaldehyde exposure it was determined that the histological changes of testes occured via FA exposure were improved. Conclusion: It was shown that harmful effects of FA on testes occured via formaldehyde exposure and lavender oil have protective effects to the these damages. Key words: Formaldehyde, Lavender Oil, Testes, Histology, Rat

Amaç: Çalışmamızda, solunum yolu ile uygulanan formaldehit'in sıçan testislerinde yaptığı hasar histolojik olarak araştırıldı. Aynı zamanda, bu hasarlara karşı aromaterapi uygulamalarında sık kullanılan lavanta yağının muhtemel koruyucu etkileri de incelendi. Gereç-Yöntem: Bu amaçla, 21 adet Wistar-Albino cinsi erkek sıçan kullanıldı. Grup I'deki sıçanlar kontrol olarak kullanılırken, Grup II'deki sıçanlar, 35 gün boyunca solunum yoluyla formaldehit'e (10 ppm/1saat) maruz bırakıldı. Grup III'deki sıçanlara ise formaldehit uygulamasının yanı sıra saf lavanta yağı (1ml/1saat) yine solunum yoluyla verildi. Uygulama sonunda hayvanlar sakrifiye edildi ve histolojik incelemeler için testisler çıkarıldı. Çalışmada, tubuli seminiferi contorti çapları, Leydig hücre sayıları ve çekirdek hasarlı Leydig hücreleri incelendi. Bulgular: Formaldehit'e maruz kalan sıçanlar kontrol grubu ile karşılaştırıldığında, tubül çapları ve Leydig hücre sayılarında azalma, çekirdek hasarlı Leydig hücrelerinde ise artma tespit edildi. Ayrıca tubül duvarlarında atrofik değişiklikler gözlendi. Formaldehit maruziyetiyle birlikte lavanta yağı uygulanan grupta ise, formaldehit maruziyetine bağlı olarak testiste gelişen histolojik değişikliklerin düzelmiş olduğu belirlendi. Sonuç: Solunum yolu ile formaldehit maruziyetine bağlı olarak testiste önemli histolojik hasarların meydana geldiği ve bu hasarlara karşı lavanta yağının koruyucu özellik gösterdiği tespit edildi. Anahtar kelimeler: Formaldehit, Lavanta Yağı, Testis, Histoloji, Rat
Solunum Yoluyla Formaldehit ve Lavanta Uygulanan Sıçan Testislerinin Değerlendirilmesi; Bir Histolojik Çalışma